From Dreams to Reality – Emigrations and Emigres in Bulgarian Cinema - Jóźwiak, Wojciech (Migrations in the Slavic Cultural Space. From the Middle Ages to the Present Day, 2022)
In socialist Bulgarian cinematography, an emigrant was most often burdened with the ideological stigma of a traitor and enemy of the people’s homeland. The emigration on the other hand was a stigmatized and marginalized phenomenon that was not given special attention. After 1989, the topic of emigration / flight and dreams of living outside the borders of the oppressive BPR became an integral part of a series of cinematic stories relating to the recent past. Pictures by artists such as Iglika Trifonova, Ilian Simeonov, Mina Mileva, Vesela Kazakova, Viktor Chuchkov, Stefan Komandarev or Ludmil Todorov not only brought up the problem of dreams about emigration / freedom, but also confronted the imagination with the often cruel reality of emigration. As a result, this prompted an image rooted in Bulgarian cinema – that of the conflict between one’s own and the foreign – to gain a new, contemporary perspective.